Rainfall Dependency and Water quality Assessment of springs of three villages of Rudraprayag District: An analysis of veins of Uttarakhand Himalaya - Chauhan , Neha; Naik , Anjali; Singh Negi, Mahavir (Acta Geographica Debrecina Landscape & Environment series, 2024)
A spring is a crevice in the substrate that forms naturally and allows water to pour out directly from the earths subsurface. Every major river in the country has a system of springs that serve as a symbolic representation of its source. But this very fundamental source of many resources is in peril. The problem is mainly related with the reduced discharge rate of water from the spring. The reason of truncate discharge rate is variability in the rainfall pattern in the recharge area due to the climate change over the years.To ensure the quality and security of the public's water supply, regular quality assessments of drinking water sources are required. In consequence, this study not only analyse the rainfall dependency of springs but also evaluated the spring water quality for drinking, using water quality index, in three villages located in Jakholi block of Rudraparayag district, Uttarakhand. The ten foremost physiochemical elements that regulate water quality—Nitrate, Fluoride, Iron, pH, Turbidity, Chloride, Residual Chlorine, Magnesium, sulphate, and Hardness—were investigated to ensure compliance with guidelines defined by the Bureau of Indian Standards IS: 12500:2012. After examining the data, it became apparent that all of the indicators pointed to acceptable water quality, making it ideal for drinking. However, because of its low discharge and great reliance on rainfall, its position is getting more detrimental.